Submission Guidelines - College of Education, The Chairperson Committee on Publications (Philippine Journal of Education Studies (formerly the Education Quarterly); Vol. 66, No. 1 (December 2008), 2010)
The Education Quarterly is the refereed journal of the College of Education, University of the Philippines, Diliman. Graduates, students, and scholars from any reputable educational/academic institution are welcome to submit their manuscripts for evaluation.